Guide to techniques in mouse development. - Wassarman, Paul M.; Soriano, Philippe M., 1953- (Methods in enzymology, 2010)
This volume comprehensively covers new technologies and methodologies that have appeared for the study of mouse development. This volume is an update of volume 225 of MIE, "Guide to Techniques in Mouse Development", edited by P.M. Wassarman and M.L. DePamphilis and published in 1993. During the past 17 years many new technologies or methodologies have appeared for the study of mouse development and this volume comprehensively covers these, including: new techniques for the cryopreservation of gametes and emb.